Obstetric risk factors and time trends of neurodevelopmental outcome at 2 years in very‐low‐birthweight infants: a single institution study. (4th August 2015) - Gardella, Barbara; Iacobone, Anna Daniela; Bogliolo, Stefano; Musacchi, Valentina; Orcesi, Simona; Tzialla, Chryssoulla; Spinillo, Arsenio
<x xml:space="preserve">Abstract</x> Aim To assess the time trends of neonatal survival and infant neurodevelopmental outcome in very‐low‐birthweight children at 24 months corrected age over a 20‐year period. Method The study cohort comprised 857 infants (439 males and 418 females) weighing less than 1500g at birth or delivered before 32 weeks gestational age in the period 1989 to 2008. Neurological examination and cognitive assessment of the infants (Bayley Scales of Infant Development and Griffiths Mental Developmental Scale) were performed at 24 months corrected age. Results The prevalence of neonatal survival with normal neurodevelopmental outcome increased from 55.3% (104/188) in 1989 to 1993, to 61.4% in 1994–1998 (116/189), 68.3% in 1999 to 2003 (138/202), and 84.5% in 2004 to 2008 (235/278) (annual increase=1%, 95% CI 2.1–4.1; p<0.001). In logistic models, the increase in the rate of normal neurodevelopmental outcome during the periods studied was consistent across the categories of birthweight (≤1000g as opposed to >1000g), gestational age (≤28wks as opposed to >28wks), and clinical characteristics (pre‐eclampsia/growth restriction as opposed to spontaneous prematurity/rupture of membranes). Interpretation The increased rate of normal neurodevelopmental outcome at 2 years among very‐low‐birthweight infants is independent of obstetric risk factors.